A filosofia da história em Arthur C. Clarke : uma relação singular com o tempo histórico no âmago da era espacial (1951-1962) - Henrique Carvalho Figueredo (2023)
This dissertation analyzes the fictional and non-fictional writing of Arthur C. Clarke, more specifically that produced between the beginning of his career and the beginning of the Space Race (1951-1962). We seek to examine the possible existence of a philosophy of history arranged throughout the textual production that constituted this writer's political and intellectual project in a context that singled out his ideas. To this end, we analyze the works The Exploration of Space (1951), Prelude to Space (1951), The City and the Stars (1956) and Profiles of the Future: An Inquiry into the Limits of the Possible (1962). In the selected sources, some narrative elements - commonly present in the way in which the philosophies of the history of modernity elaborated historical time - were mapped out based on a concern with the persistence of the relationship with historical time sustained by the philosophy of progress, identified in a new way in the studied period. Elements such as a conception of history, historical purpose, historical dynamics, the engine of history, human nature, historical agency and the present, past and future, guided the present investigation. We analyze how these elements were appropriated by Clarke based on the specificities of his linguistic and social context. For this, we relate the author's intellectual performance with the characteristics of the expression of his ideas in each work, taking into account the social insertion of each one and its type. We thus obtained a historicized image of Clarke's discursive production that reveals the tradition of elaboration of historical time which he gave vent to when proposing his project, despite his verbalized intentions. Such a project, based on the available linguistic resources and the social demands of its context, aimed at a transformation of the world that, in its discursive translation, expressed an optimistic and scientistic philosophy of humanity's history.